PENGARUH DISIPLIN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PABRIK MINYAK KAYU PUTIH (PMKP) DI KRAI PURWODADI - Adi Prawatya, Dipta; Toto Rahardjo, Susilo (Diponegoro Journal of Management, 2012)
On everyone working or in a workgroup, the performance always expected to be always good quality and quantity. To get the result itself must be backed up with goal-setting and to be begun with the rational work planning. Performance goal-setting intention is compiled targets useful not only as guidelines for achieving the objectives, but can also be a means of performance evaluation at the end of the period and to manage the state of postgraduate work during that period. Many factors can affect the performance of employees, such as the discipline of work and organisational culture. The object of this research Pabrik Minyak Kayu Putih (PMKP) in the village of Krai, district Toroh, Grobogan, Purwodadi. Reasons to take an object on Pabrik Minyak Kayu Putih (PMKP) in Purwodadi, because the results of the survey obtained information that the pre a few employees showed inadequate performance, such as late attendance, at the time of the break of the afternoon, return to the office which is supposed to 13.00 till 13.30 even more, or are not in place, although present in the workplace. If the employee could not improve its performance through the discipline of work and organisational culture that is already good, means the performance of employees tends to be low. The purpose of this research is to analyze the effect of work discipline and organizational culture on performance Pabrik Minyak Kayu Putih (PMKP) in Purwodadi. Populations and samples in this study are employees of Pabrik Minyak Kayu Putih (PMKP) in Purwodadi that add up to 40 employees. Its data type is primary. Method of data collection using the questionnaire. Analysis technique used is multiple regression. Results of analysis using SPSS Version 13 shows that: (1). work discipline influential positive and significant to the performance of employees. (2) organizational culture influential positive and significant effect on employee performance.